The role of phonological awareness, rapid automatized naming, and verbal working memory in developmental dyslexia : implications for the double-deficit hypothesis - Chan, Sharon Shi Ning (2016)
Developmental dyslexia is one of the most prevalent developmental disabilities in Singapore (Dyslexia Association of Singapore, n.d.). Three core behavioural deficits have been identified to account for the reading difficulties observed in children with dyslexia. Despite extensive research examining the pertinent role of phonological awareness (PA) and rapid automatized naming (RAN) in reading, the role of verbal working memory (VWM) is not as well established. The double-deficit hypothesis (Wolf & Bowers, 1999) is a prevailing explanation for developmental dyslexia that posits PA and RAN are two independent core deficits. Hence, the present study conducted a behavioural investigation into these three core behavioural deficits and their relative role in reading. 17 participants with developmental dyslexia and 13 healthy controls were given a battery of neurocognitive tests. Aligned with past literature, participants with dyslexia exhibited poorer performance across all domains compared to the control group. However, contrary to most research and the double- deficit hypothesis (Wolf & Bowers, 1999), significantly poorer performance was not found for PA and RAN. In addition, only VWM significantly correlated with, and emerged as a significant predictor of, reading. As a whole, our results cast doubt on the role of PA and RAN in reading, highlight the importance of VWM involvement in the process of reading, and suggest the need for further refinement of the double- deficit hypothesis (Wolf & Bowers, 1999).